2021
DOI: 10.1186/s13048-021-00846-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of the PI3K/PTEN/Akt and mTOR signalling pathways limits follicle activation induced by ovarian cryopreservation and in vitro culture

Abstract: Background Cryopreservation and transplantation of ovarian tissue (OTCTP) represent a promising fertility preservation technique for prepubertal patients or for patients requiring urgent oncological management. However, a major obstacle of this technique is follicle loss due to, among others, accelerated recruitment of primordial follicles during the transplantation process, leading to follicular reserve loss in the graft and thereby potentially reducing its lifespan. This study aimed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 82 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…It is essential to replace culture medium after a fixed amount of time in order to prevent nutrient depletion and ensure elimination of toxic waste products, like ammonia and lactic acid. In studies involving IVC for more than four days, standard practice is to replace half of the culture medium every other day [ 10 , 21 , 38 , 50 , 51 , 52 , 53 ].…”
Section: Follicle Activation: From Pmfs To Secondary Folliclesmentioning
confidence: 99%
“…It is essential to replace culture medium after a fixed amount of time in order to prevent nutrient depletion and ensure elimination of toxic waste products, like ammonia and lactic acid. In studies involving IVC for more than four days, standard practice is to replace half of the culture medium every other day [ 10 , 21 , 38 , 50 , 51 , 52 , 53 ].…”
Section: Follicle Activation: From Pmfs To Secondary Folliclesmentioning
confidence: 99%
“…Therefore, the ability of miRNA to target PTEN has attracted the attention of many researchers. Multiple studies have shown that exosomal miR-21 can regulate the proliferation of multiple cells (33,37,38). In our study, we simulated the process of miRNA delivery through the lipid shell of exosomes and transferred miR-21 mimics and inhibitors into HUVECs for observation.…”
Section: F G Hmentioning
confidence: 99%
“…The development of primordial follicles requires two-way signals to communicate with surrounding somatic cells (i.e., granulosa cells), where particular cytokines and growth factors are involved [8] . PI3K/PTEN/serine/threonine kinase (AKT) signaling, for instance, is related to the fate of primordial follicles [9,10] . Moreover, rapamycin, an inhibitor of mTOR, is known to suppress excessive activation of primordial follicles and protect the ovarian reserve by receiving regulatory signals from upstream AKT [11,12] .…”
Section: Primordial Follicle Activation Depends On the Hippo Signalin...mentioning
confidence: 99%